2009
DOI: 10.1248/bpb.32.1649
|View full text |Cite
|
Sign up to set email alerts
|

Chlorpyrifos Induces Delayed Cytotoxicity after Withdrawal in Primary Hippocampal Neurons through Extracellular Signal-Regulated Kinase Inhibition

Abstract: Organophosphorus (OP) pesticides are extensively used for control of insects around the home and in agricultural practice. However, they can pose a threat to public health. OP pesticides are known to cause millions of acute poisoning cases per year around the world.1) Besides acute poisoning, OP pesticide exposure causes chronic neurological consequences, especially those related to poor neuropsychiatric changes or neurobehavioral performances in some cognitive domains or mood domain.2) The chronic neurologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…This is accompanied by a drastic decrease in the frequency of mEPSCs, slowing of mEPSC kinetics, and decreased input resistance of CA1 neurons in CPF-treated mice. Although our results are in line with reports of CPF-induced delayed cytotoxicity in vitro (Rush et al, 2010;Tan et al, 2009;Terry et al, 2003), we did not observe any change in neuron number in either the CA3 or CA1 regions with treatment in vivo. However, we did observe a large novel decrease in synaptic spine density across both basilar and apical dendrites of CA1 neurons, indicating that synaptic spine loss rather than neuron loss is responsible for the decrease in basal hippocampal synaptic transmission at 3 months following CPF treatment.…”
Section: Early Versus Delayed Effects Of Repeated Subclinical Cpf Treatmentsupporting
confidence: 90%
“…This is accompanied by a drastic decrease in the frequency of mEPSCs, slowing of mEPSC kinetics, and decreased input resistance of CA1 neurons in CPF-treated mice. Although our results are in line with reports of CPF-induced delayed cytotoxicity in vitro (Rush et al, 2010;Tan et al, 2009;Terry et al, 2003), we did not observe any change in neuron number in either the CA3 or CA1 regions with treatment in vivo. However, we did observe a large novel decrease in synaptic spine density across both basilar and apical dendrites of CA1 neurons, indicating that synaptic spine loss rather than neuron loss is responsible for the decrease in basal hippocampal synaptic transmission at 3 months following CPF treatment.…”
Section: Early Versus Delayed Effects Of Repeated Subclinical Cpf Treatmentsupporting
confidence: 90%
“…The augmented cell loss reflects the fact that the two agents reduce cell number through different mechanisms; chlorpyrifos is directly antimitotic and proapoptotic (Qiao et al, 2001; Rush et al, 2010; Slotkin and Seidler, 2012; Song et al, 1998; Tan et al, 2009), whereas dexamethasone enhances the switch from cell replication to neurodifferentiation (Ebert et al, 1997; Jameson et al, 2006b). Notably, these effects were seen at exposures that are not cytotoxic (Jameson et al, 2006b; Qiao et al, 2001; Song et al, 1998), and indeed, dexamethasone actually promotes cell viability (Jameson et al, 2006b).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with two activators of ERK1/2, such as nerve growth factor (NGF) and carbachol, inhibited the delayed neurotoxicity induced by CPF, which shows the influence of the inhibition of ERK1/2 phosphorylation on the delayed neurotoxicity caused by CPF [40].…”
Section: Organophosphorus Compound-induced Neurodegenerative Diseasesmentioning
confidence: 97%
“…In addition, chronic exposure to OPCs caused delayed neuropsychiatric disorders, and a mechanism underlying the delayed neurotoxicity induced by CPF can be the inhibition of ERK1/2 signaling activation. In this context, it was shown that phosphorylation of ERK1/2 during a 96-h exposure to 10 µM CPF occurred but that withdrawal after 48 h of exposure to this agent caused ERK1/2 signal inhibition, which delayed toxicity of CPF in primary rats hippocampal neurons [40].…”
Section: Organophosphorus Compound-induced Neurodegenerative Diseasesmentioning
confidence: 99%
See 1 more Smart Citation